2021
DOI: 10.1111/febs.16051
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of innate immune responses by cell death‐associated caspases during virus infection

Abstract: Viruses are obligate intracellular pathogens that rely on cellular machinery for successful replication and dissemination. The host cells encode a number of different strategies to sense and restrict the invading viral pathogens. Caspase‐mediated programmed cell death pathways that are triggered by virus infection, such as apoptosis and pyroptosis, provide a means for the infected cells to limit viral proliferation, leading to suicidal cell death (apoptosis) or lytic cell death and alerting uninfected cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 104 publications
(173 reference statements)
2
10
0
Order By: Relevance
“…Our finding, that caspase inhibition increases interferon signaling, is consistent with previous studies showing caspase-dependent suppression of the cGAS–STING–IFN pathway during DNA virus infection [reviewed in ( 23 )]. A previous study has reported that caspase inhibition also can increase radiation-induced IFN secretion ( 36 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding, that caspase inhibition increases interferon signaling, is consistent with previous studies showing caspase-dependent suppression of the cGAS–STING–IFN pathway during DNA virus infection [reviewed in ( 23 )]. A previous study has reported that caspase inhibition also can increase radiation-induced IFN secretion ( 36 ).…”
Section: Discussionsupporting
confidence: 93%
“…The underlying molecular mechanism of how pan-caspase inhibition increases the IFN response after IR and ATRi remains to be elucidated. Caspases may potentially cleave cGAS or other factors in the cGAS–STING signaling cascade ( 23 , 37 ). Furthermore, the previous study with radiation-induced IFN suggested that caspase inhibition prevents breakdown of irradiated cells with cytosolic DNA ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different immune cell types limit viral proliferation by inducing suicidal apoptotic pathways or by entering lytic cell death and by alerting neighbouring cells to mount pyroptotic responses. Fang and Peng [14] describe in their review how viruses trigger or dampen caspase activation and how this affects innate immune responses to viral infection. Extensive innate immune signalling and inflammation can undermine protective responses during infection and tissue injury, in particular, when they are not terminated accurately.…”
Section: Figmentioning
confidence: 99%
“…However, when the body is subjected to severe damaging stimuli, such as the disturbance of the body's internal environment caused by inflammation or biochemical stimulation, the cells of the body will undergo apoptosis caused by aspartate-specific cysteine proteases known as caspases. Cell apoptosis is closely related to mitochondria besides some signaling pathways in the cytoplasm [ 20 ]. Apoptosis caused by mitochondrial pathway is mainly related to the mitochondrial serine protease Omi/HtrA2, which exists in the inner and outer membrane of mitochondria under physiological conditions and is mainly involved in clarifying misfolded proteins in mitochondria [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%